Social factors associated with tobacco and alcohol consumption in Mexican adolescents from populations under 100 000 inhabitants - Emmanuel González-Bautista; Luis Zavala-Arciniega; Leonor Rivera-Rivera; Ahidée Leyva-López; Guillermina Natera-Rey; Luz Myriam Reynales-Shigematsu (Instituto Nacional de Salud Pública, 2019)
Objective. To evaluate the social factors associated with tobacco and alcohol consumption in Mexican adolescents from populations under 100 000 inhabitants. Materials and methods. Cross-sectional study based on the National Health and Nutrition Survey (Ensanut100k). It included adolescents between 10-19 years. Adjusted logistic regression models were estimated, obtaining Odds Ratio (OR) and confidence intervals 95% (CI95%). Results. Prevalence of tobacco consumption in the last month was 5.5% (10-14 years= 1.0%, 15-19 years= 11.2%); alcohol consumption 9.3%, and excessive alcohol consumption, 2.8%. Associated factors: smoking, sex (male, OR=6.00, CI95%: 2.89-12.46), age (OR=1.73, CI95%: 1.46-2.04), remunerated work (OR=2.87, CI95%: 1.12-7.34), affiliation to health services (OR=0.26, CI95%: 0.08-0.82); alcohol consumption, (male, OR=5.11, CI95%: 2.38-11.00), age (OR=1.70, CI95%: 1.51-1.92), remunerated work (OR=2.51, CI95%: 1.01-6.24). Conclusions. To reduce the consumption of alcohol and tobacco in adolescents, comprehensive prevention strategies must be implemented that consider the individual and social context.